(untitled) (Baghdad Science Journal, 2022)
In a connected graph , the distance function between each pair of two vertices from a set vertex is the shortest distance between them and the vertex degree denoted by is the number of edges which are incident to the vertex The Schultz and modified Schultz polynomials of are have defined as: respectively, where the summations are taken over all unordered pairs of distinct vertices in and is the distance between and in The general forms of Schultz and modified Schultz polynomials shall be found and indices of the edge – identification chain and ring – square graphs in the present work.